DERIVATIONAL AFFIXES FORMING NOUN IN FIREFLY LANE NOVEL BY KRISTIN HANNAH - Ni Luh Putu Ardiningsih; I Komang Sulatra; Putu Devi Maharani (Yavana Bhasha : Journal of English Language Education, 2021)
This study aims to find out the types of derivational affixes forming noun and the functions ofderivational affixes forming noun in the novel entitled Firefly Lane written by Kristin Hannah. Themethods used in this study are quantitative and qualitative methods. This study used observationmethod in collecting the data from all chapters in the novel Firefly Lane.Finally, this writing concludesthat there were two functions of derivational affixes such are: class changing affixes and classmaintaining affixes and each function has two types which are: prefixes and suffixes. The result of thestudy found there are 3 prefixes forming noun such are: re-, pre-,and pro-, and from suffixes therewere found 22 suffixes forming noun, they are: -er, -hood, -ism, -ist, -ity, -ship, -ness, -th, -ize, -less, -ous,-y, -ful, -ive, -ing, -ance, -ence, -ant, -ion, -ment, - or, and –ure.